Numerical modelling of reinforced unpaved roads - Burd, H; Houlsby, G (Elsevier, 1989)
A finite element model capable of computing the behaviour of a reinforced unpaved road deforming in plane strain is described. Elastic perfectly-plastic soil models are used which are based on the use of the von Mises yield function for cohseive soils and the Matsuoka criterion for frictional material. The reinforcement is modelled using elastic membrane elements. The formulation is based on a large strain, large displacement Eulerian approach. The finite element model is used to back-analyse laboratory scale model tests in which a footing is jacked monotonically into a model reinforced unpaved road. Some selected results of these back-analysis calculations are presented. -Authors